2013
DOI: 10.21608/jssae.2013.52899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Stress, Biofertilizers and Nitrogen Application Rates on Cowpea Yield and Some Water Relations in the North Middle Nile Delta Region

Abstract: Two field experiments were carried out at Sakha Agricultural Research station (31 o o5` N latitude and 30 o 57` E longitude) Kafr El-Sheikh governorate during the two successive summer growing seasons 2012 and 2013 to investigate the effect of water stress through various growth stages, biofertilizers and nitrogen application rates on cowpea yield, its components, uptake of phosphorus, nitrogen and protein content in some plant organs and some water relations in the North Middle Nile Delta region. A split spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Adding 40 kg N/fad., significantly increased plant height, number of leaves/ plant, number of branches/plant and chlorophyll content in both seasons (El-Atawy and Kasem, 2011; Moursi et al, 2013). Fertilization of cvs Cream-7 and Dokki-331 with rhizobium at 200 g/fad., and mineral at 45 or 60 kg N/fad., increased dry weight of leaves and total dry weight/plant (Attia, 2012).…”
Section: Dry Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding 40 kg N/fad., significantly increased plant height, number of leaves/ plant, number of branches/plant and chlorophyll content in both seasons (El-Atawy and Kasem, 2011; Moursi et al, 2013). Fertilization of cvs Cream-7 and Dokki-331 with rhizobium at 200 g/fad., and mineral at 45 or 60 kg N/fad., increased dry weight of leaves and total dry weight/plant (Attia, 2012).…”
Section: Dry Weightmentioning
confidence: 99%
“…N Fertilization at 45or 60kg/fad., of cvs Cream-7 and Dokki-331, increased dry weight of leaves and total dry weight/ plant, and seed yield per plant and per fad., in both seasons (Attia,2012). Adding 40 kg N/fad., significantly increased plant height, number of leaves/plant, number of branches /plant and chlorophyll content in both seasons, while adding 30 kg N/fad., gave the highest mean values of seed yield/ plant, seed yield/fad., number of pods/ plant and 100-seed weight (El-Atawy and Kasem, 2011 ; Moursi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also, co-inoculation with Paenibacillus polymyxa and Rhizobium tropici enhancement growth, nitrogen content, and nodulation of common bean (Phaseolus vulgaris L.) under a water-deficit environment (Figueiredo et al, 2008). Also, Moursi et al (2013) showed that application of cowpea with rhizobium and different rates of nitrogen enhancement yield and yield components, nitrogen, phosphorus % and protein content under the highest mean values for water productivity and productivity of applied irrigation water.…”
Section: Introductionmentioning
confidence: 98%